Cote d'Ivoire : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Cote d'Ivoire. (IMF Staff Country Reports; Country Report ;, 2016)
This paper describes the recent economic developments and economic outlook and risks of the Cote d'Ivoire's economy. Over the past four years, Cote d'Ivoire's economic performance has been impressive, in sharp contrast with the preceding 10 years marked by conflicts and economic stagnation. Growth has been accompanied by a modest decline in poverty, but other human development indicators have been slow to improve. Financial sector vulnerabilities could trigger a shock to the economy or reinforce the impact on the real sector of nonfinancial shocks, potentially generating self-reinforcing adverse spillover effects on the economy in the absence of countervailing policy action.